Città tra mare e laguna: da Santa Gilla a Cagliari Aspetti archeologici, geologici, storici, insediativi e sociali Tomo I - Martorelli, Rossana; Serreli, Giovanni; Mele, Maria Grazia R.; Nocco, Sebastiana (RESOCONTI, 2023)
This volume contains the Proceedings of the Conference held on October 19 and 20, 2022, in Cagliari, Italy, at the Boscolo Lecture Hall of the Institute of History of Mediterranean Europe of the National Research Council (CNR-ISEM) to illustrate the results achieved during the conduct of a two-year research project "Cities between sea and lagoon: from Santa Gilla to Cagliari. Archaeological, geological, historical, settlement and social aspects, funded under Regional Law Aug. 7, 2007, No. 7: "Promotion of scientific research and technological innovation in Sardinia. basic research projects," presented by CNRISEM (PI Marcello Verga, succeeded by Maria Grazia Mele), together with the University of Cagliari (coordin. of Research Unit No. 1 Rossana Martorelli). The Project examined the current territory of Cagliari from a "between sea and lagoon" reading perspective, tracing the historical events and the geological and archaeological phenomena of the various settlements, from the Judicial citadel of Sancta Caecilia, Ilia, Ygia, on the shores of the Santa Gilla Lagoon, to the Castel di Castro/Caller with its Appendices of medieval and modern times. Following the same time frame, the Proceedings of the Conference sees the light of day in two parts, the first of which focuses on the historical-urban affairs of the buried and almost forgotten Sancta Caecilia, Sancta Ygia. The second, on the other hand, deals with Cagliari in the modern age, focusing on the political-institutional, economic, social and settlement aspects of the port district, which was more linked to the lagoon and the sea, as with other cities of the Hispanic Monarchy.